Synthesis of Porous δ‐MnO2 Submicron Tubes as Highly Efficient Electrocatalyst for Rechargeable Li–O2 Batteries. Issue 11 (5th May 2015) - Zhang, Peng; Sun, Dongfei; He, Mu; Lang, Junwei; Xu, Shan; Yan, Xingbin
Abstract: Lithium–oxygen (Li–O2 ) batteries are receiving intense interest because of their high energy density. A new tubular δ‐MnO2 material prepared by a simple hydrothermal synthesis is an efficient electrocatalyst for Li–O2 batteries. The synthesized δ‐MnO2 exhibits a unique tubular structure, in which the porous walls are composed of highly dispersed ultrathin δ‐MnO2 nanosheets. Such a unique structure and its intrinsic catalytic activity provide the right electrocatalyst characteristics for high‐performance Li–O2 batteries. As a consequence, suppressed overpotentials—especially the oxygen evolution reaction overpotential—superior rate capability, and desirable cycle life are achieved with these submicron δ‐MnO2 tubes as the electrocatalyst. Remarkably, the discharge product Li2 O2 of the Li–O2 battery exhibits a uniform nanosheet‐like morphology, which indicates the critical role of the δ‐MnO2 in the electrochemical process, and a mechanism is proposed to analyze the catalysis of δ‐MnO2 . Abstract : Battery powered: Tubular δ‐MnO2 is developed by a facile template‐induced hydrothermal method. The synthesized δ‐MnO2 exhibits a porous tube wall assembled by highly dispersed tiny nanosheets, which facilitates the diffusion of electrolyte and oxygen. As an electrocatalyst in Li–O2 batteries, the δ‐MnO2 tubes exhibit suppressed overpotentials, superior rate properties, and good cycle stability.